Factors Related to Nurses' Behavior Regarding BTCL (Basic Trauma Cardiac Life Support ) in Implementing Emergency Measures at Cendrawasih Dobo Regional Hospital: Factors Influencing Nurses’ BTCLS Practice - Pattimura, Nastain Abubakar; Makatita , Sakina (CV. Paperhome Indonesia, 2025)
Background: Basic Trauma Cardiac Life Support (BTCLS) is an action to provide assistance to victims of disasters or emergencies to prevent death or organ damage so that their productivity can be maintained at the level before the disaster or emergency event occurred. Objective: To determine the factors related to nurses' behavior regarding BTCLS in implementing emergency measures at Cendrawasih Dobo Regional Hospital . Method: The type of research used in this study is quantitative analytical descriptive research with a cross-sectional study approach using the Cross Sectional Study Test with a sample size of 32 respondents. Results: From the analysis results obtained a significance value between the relationship between knowledge and nurses' behavior about BTCLS of (p = 0.011), which means there is a significant relationship between knowledge and nurses' behavior about BTCLS in the implementation of emergency measures at Cendrawasih Dobo Regional Hospital and for attitudes and nurses' behavior about BTCLS of (p = 0.491) which means there is no significant relationship between attitudes and nurses' behavior about BTCLS (Basic Trauma Cardiac Life Support) in the implementation of emergency measures at Cendrawasih Dobo Regional Hospital . Conclusion: There is a significant relationship between the relationship between knowledge and nurses' behavior about BTCLS in the implementation of emergency measures at Cendrawasih Dobo Regional Hospital, and there is no significant relationship between attitudes and nurses' behavior about BTCLS in the implementation of emergency measures at Cendrawasih Dobo Regional Hospital.